Experimental study of the strength of hip endoprosthesis elementsmade by 3D printing - Korzh, Mykola; Makarov, Vasyl; Shidlovsky, Mykola; Yermakov, Vladlen; Nikitin, Yurii; Pidgaiska, Olga; Tankut, Оleksiy; Karpinsky, Mykhaylo; Karpinska, Olena; Zakhovayko, Olexandr; Chupryna, Dmytro (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Тhree-dimensional printing of porous titanium implants is a promising area of additive production in orthopedic surgery. The question remains relevant mechanical strength and durability of such device. Objective. Determine in the experiment the strength of the stem, the neck of the stem and the cups of hip endoprosthes made by 3D-printing from titanium alloy, and compare with a similar rate of serial implants. Methods. The strength of the stem and cups of hip endoprostheses made by 3D-printing on an Arcam printer from titanium alloy TI6AL4V was studied. Serials hip implants made form titanium alloy. There were 3 samples of hip endoprostheses for each test. Stems of endoprostheses were examined on the TIRATEST-2300 machine under the conditions of loading on a three-point bend, the necks of stems were examined under the influence of combined load on the bend with a shift, the cups were examined on compression. Results. Tensile strength in the case of three-point bending of the stems of implants made by mechanical processing and 3D printing did not have any differences significantly (p = 0.146) and was (1480.62 ± 62.50) MPa and (1396.88 ± 50.90) MPa, respectively. The necks of stems of serial endoprostheses and made by 3D-printing had a comparable limit of strength — (408.61 ± 1.25) MPa and (403.49 ± 8.99) MPa, respectively (p = 0.384). Under the conditions of compression tests of cups of endoprostheses all the samples withstood a load of 98.0 kN without any signs of destruction. Conclusions. The values of the tensile strength of the components of serial implants and those made by 3D-printing did not differ statistically significantly. Thus, 3D-porous structures have significant potential for creation of elements of hip endoprostheses.